The Performance Analysis of the Infrared Photodiode Sensor to Infusion Set on Infusion Device Analyzer Machine - Anisa Rahma Astuti; Syaifudin; Triana Rahmawati; Khongdet Phasinam (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
Infusion pumps and syringe pumps are devices used to administer liquid medicines to patients. The frequency of using the infusion pump and syringe pump in the long term will affect the accuracy of the tool. Accuracy is very important in dosing to patients in critical conditions who require intensive care to prevent fluid balance in the body. Therefore, periodic calibration of medical devices is required at least once a year. Calibration according to Permenkes No. 54 of 2015 is a calibration activity to determine the correctness of a tool. The purpose of this research is to make an Infusion Device Analyzer (IDA) with a TFT LCD displaying a graph of flowrate parameters. The method used is to analyze the flowrate value using an infrared photodiode sensor and can see the stability of the flowrate graph on a 7-inch TFT LCD from the use of 2 brands of syringes and an infusion set. The results obtained can be stored on the SD Card. The measurement results show that the error in the performance of the syringe and infusion pump read by the module on Channel 1 with the Terumo syringe is 0.15 (10 ml/h), 0.1 (50ml/h) and 0.03 (100ml/h). . On Channel 2 it is 0.02(10ml/hour), 0.03 (50ml/hour) and 0.04(100ml/hour). When using the B-Braun Channel 1 syringe, 0.25 (10ml/h), 009(50ml/h) and 0.08(100ml/h) are used. And on Channel 2 it is 0.62 (10ml/h), 0.15 (50ml/h), and 7.3 (100ml/h). When using the Terumo Channel 1 brand infusion set at 0.05 (10ml/h), 0.3(50ml/h), and 0.04(100ml/h). On Channel 2 it is 0.14(10ml/hour), 0.02 (50ml/hour) and 0.18 (100 ml/hour). When using the B-Braun Channel 1 Infusion Set, it is 0.07(10ml/h), 0.02(50 ml/h), and 0.03 (100ml/h). Then on Channel 2 0.07 (10ml/hour), 0.02(50 ml/hour), and 0.1(100ml/hour). The conclusion of this study is that the use of 2 different infusion sets greatly affects the readings, other than that other factors can also affect the readings including the position of the hose and the placement of sensors on each channel. From the manufacture of this tool, it is expected that users can be more efficient in using a 2-channel Infusion Device analyzer which can be run at the same time.